Library information resources in the era of global insecurity (2020)
Securing library information resources and facilities in the era of global insecurity is germane in building confidence and a sense of security among stakeholders and prevent theft by unscrupulous and criminally minded individuals. As a result of this, the paper explores the concept of information resources, discusses the broad categorization of information resources as well as explain the features, approaches and strategies for securing library information resources. The paper identifies the challenges confronting the use of electronic security systems in libraries in Nigeria to include inadequate funding of library, power failure, hardware and software failure, inadequate skilled manpower among others. It is recommended that consistent disbursement of funds for library projects, promotion of library education among librarians and other para-professionals, constant power supply to the library as well as training of IT professionals in core areas of library management to provide tailor-made technological supports for optimal operations of the library services would help to effectively manage library information resources in the era of global insecurity.